Checkpoint Activation of an Unconventional DNA Replication Program in Tetrahymena - Sandoval, Pamela Y. (Public Library of Science, 2015)

(untitled) (PLoS Genet)
The intra-S phase checkpoint kinase of metazoa and yeast, ATR/MEC1, protects chromosomes from DNA damage and replication stress by phosphorylating subunits of the replicative helicase, MCM2-7. Here we describe an unprecedented ATR-dependent pathway in Tetrahymena thermophila in which the essential pre-replicative complex proteins, Orc1p, Orc2p and Mcm6p are degraded in hydroxyurea-treated S phase cells. Chromosomes undergo global changes during HU-arrest, including phosphorylation of histone H2A.X, deacetylation of histone H3, and an apparent diminution in DNA content that can be blocked by the deacetylase inhibitor sodium butyrate. Most remarkably, the cell cycle rapidly resumes upon hydroxyurea removal, and the entire genome is replicated prior to replenishment of ORC and MCMs. While stalled replication forks are elongated under these conditions, DNA fiber imaging revealed that most replicating molecules are produced by new initiation events. Furthermore, the sole origin in the ribosomal DNA minichromosome is inactive and replication appears to initiate near the rRNA promoter. The collective data raise the possibility that replication initiation occurs by an ORC-independent mechanism during the recovery from HU-induced replication stress.